Neisseria sicca Endocarditis Complicated by Intracranial and Popliteal Aneurysms in a Patient with a Bicuspid Aortic Valve. (5th February 2013) - Debellemanière, Guillaume; Chirouze, Catherine; Hustache-Mathieu, Laurent; Fournier, Damien; Biondi, Alessandra; Hoen, Bruno
Abstract : We report a case of infective endocarditis due to Neisseria sicca complicated by intracranial and popliteal aneurysms and hepatic and splenic infarcts in a patient with a bicuspid aortic valve. No predisposing factor other than poor dental condition was found. The patient fully recovered after antibiotic therapy, aortic and mitral valve replacement, endovascular occlusion of the middle-cerebral artery aneurysm, and surgical treatment of the popliteal artery aneurysm.